FORECASTING THE CLOSING PRICE OF META STOCKS USING A PULSE FUNCTION INTERVENTION ANALYSIS APPROACH - Mardianto, M. Fariz Fadillah; Faizun, Nurin; Nauvaldy, Muhammad; Sediono, Sediono (MEDIA STATISTIKA, 2025)
Meta Platforms, Inc. (META), the holding company that owns Facebook, Instagram, and WhatsApp, plays a crucial role in advancing artificial intelligence (AI). In early 2024, CEO Mark Zuckerberg announced an ambitious initiative to develop Artificial General Intelligence (AGI), leading to a significant rise in Meta's stock during the first quarter. Consequently, an analysis using the pulse function intervention method was conducted to model and forecast future data. The study utilized weekly data consisting of 124 training and 7 testing observations, spanning from March 13, 2022, to September 15, 2024. The optimal intervention model determined is ARIMA (0,2,1), with parameters (0,0,1) and an intervention point at t = 99. Predictions for a further 8 periods resulted a MAPE of 9.682003% and an MSE of 2411.771. These findings suggest that investors should consider the influence of Zuckerberg's AGI strategy announcement on stock performance. The post-announcement surge indicates a favorable market reaction, and investors should closely follow the AGI project's development to assess META's long-term potential in the technology sector.